Simulation of Structural Transformations in Modified Near-Surface Layers of Crystals; Materials Science Forum; Vol. 970 : Modern Problems in Materials Processing, Manufacturing, Testing and Quality Assurance II - Borodin Yu. V. Yuri Viktorovich (2019, 2019)
Title screen